PP.06.32: ASSOCIATION BETWEEN URIC ACID, METABOLIC VARIABLES AND ARTERIAL STIFFNESS IN THE EARLY PHASE OF HYPERTENSION. (June 2015) - Saladini, F.; Benetti, E.; Fania, C.; Mos, L.; Garbelotto, R.; Mazzer, A.; Casiglia, E.; Palatini, P.
Abstract : Objective: High serum uric acid (SUA) is often associated with the metabolic syndrome and is a risk factor for cardiovascular disease. Whether high SUA is associated with arterial stiffness in the early stage of hypertension is not well known. Design and method: We addressed this issue in 340 non-diabetic subjects from the HARVEST study (73% males) with a mean age of 31 ± 8 years and a mean blood pressure (BP) of 145 ± 11/92 ± 6 mmHg. Patients were divided into SUA tertiles (T1: 1.30–4.47, T2: 4.50–5.50, T3: 5.55–8.60 mg/dl). Arterial stiffness was assessed by pulse wave velocity (PWV), augmentation index (AIx), pulse pressure (PP) amplification and systolic BP (SBP) amplification. Results: Patients in the highest SUA tertile were heavier (BMI, T3: 25.7 ± 0.3 kg/m2, T2: 24.9 ± 0.3 kg/m2, T1: 24.4 ± 0.3 kg/m2; p = 0.031) and had a worse metabolic profile, with higher age-and-sex-adjusted total cholesterol (TC) (T3: 201.5 ± 3.8 mg/dl, T2:188.8 ± 3.6 mg/dl, T1:193.2 ± 3.8 mg/dl; p = 0.048), triglycerides (T3: 150.9 ± 7.8 mg/dl, T2: 99.6 ± 7.5 mg/dl, T1: 96.3 ± 7.7 mg/dl; p < 0.0001) and glucose (T3: 93.0 ± 1.1 g/dl, T2: 92.6 ± 1.1 g/dl, T1: 89.5 ± 1.1 mg/dl; p = 0.059), and lower HDL-C (T3: 50.6 ± 1.6 mg/dl, T2: 54.9 ± 1.6 mg/dl, T1: 56.8 ± 1.7 mg/dl; p = 0.033) than subjects in the lower SUA tertiles. No significant difference in peripheral BP and central BP was found according to SUA tertile. Patients in the highest SUA tertile showed lower SBP amplification (p = 0.037 adjusted for age, sex, BMI, and metabolic data). This difference remained significant after inclusion in the model of lifestyle habits (p = 0.021) and of 24-h BP and heart rate (p = 0.034). Patients in the highest SUA tertile also presented a lower PP amplification even though the difference was of borderline significance after adjustment for age, sex and metabolic data (p = 0.08). No significant difference in PWV and AIx was found across SUA tertiles. Conclusions: These data show that among young to middle-age stage I hypertensives higher SUA is associated with metabolic abnormalities and initial impairment of arterial elasticity.